The effect of guideline-directed medicine on patients with new-onset heart failure following acute myocardial infarction - Lei, Mengjie; Wang, Jingyao; Wang, Xiao; Sue, Xue; Li, Cairong; Yang, Yanli; Li, Yachao; Zhao, Zhigang; Xue, Zengming (Frontiers in Cardiovascular Medicine, 2025)
AimsTo investigate the impact of guideline-directed medical therapy (GDMT) during hospitalization on the prognosis of patients with heart failure (HF) episode complicating post-acute myocardial infarction (AMI).MethodsFrom 01/05/2017 to 30/09/2022, 527 patients with HF episode complicating post-AMI at a single medical center who were retrospectively analyzed. Based on whether GDMT during hospitalization was used in patients undergoing percutaneous coronary intervention (PCI), the patients were divided into the GDMT group (n = 379) and the non-GDMT group (n = 148), with a follow-up period of 12 months after PCI. The primary endpoint was the composite endpoint of all-cause death and all-cause readmission.ResultsThe incidence of the primary endpoints (7.9% vs. 18.9%, P < 0.001), cardiac death and cardiac readmission composite events (5.5% vs. 15.5%, P = 0.002), all-cause readmission events (7.1% vs. 18.9%, P < 0.001), and cardiac readmission events (5.0% vs. 13.5%, P = 0.001) in the GDMT group were lower. Cox regression analysis revealed that the incidence of primary endpoints, cardiac death and cardiac readmission composite events, all-cause readmission events, and cardiac readmission events in patients treated with GDMT during hospitalization were 0.266 times (HR 0.266; 95% CI 0.146–0.487; P < 0.001), 0.282 times (HR 0.282; 95% CI 0.137–0.581; P = 0.001), 0.251 times (HR 0.251; 95% CI 0.136–0.464; P < 0.001) and 0.262 times (HR 0.262; 95% CI 0.125–0.551; P < 0.001), respectively, compared to patients treated without GDMT.ConclusionFor patients with HF episode complicating post-AMI who undergo PCI, the use of GDMT during hospitalization reduces the incidence of primary endpoints, cardiac death and cardiac readmission composite endpoints, and all-cause readmission and cardiac readmission.